The Relationship Between Parental Alienation Syndrome and Depression Levels Among Adolescents Aged 13–17 Years from Divorced Families - Saadet İrem Efe; Zeynep Çetin (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objectives: This study aimed to examine parental alienation in the context of divorce and evaluate its relationship with depression levels among adolescents aged 13–17 years.Materials and Methods: This cross-sectional correlational study included 52 adolescents aged 13–17 years who were receiving divorce-related counselling services. Data were collected using the Parental Alienation Questionnaire and the Beck Depression Inventory. The relationship between parental alienation and depression was evaluated using Spearman correlation analysis.Results: A moderate, positive, and statistically significant association was found between parental alienation and depression levels (ρ = .608, p < .001).Conclusion: Higher parental alienation levels were associated with greater depressive symptom severity among adolescents from divorced families. The findings highlight the importance of assessing parent–adolescent relationships and adolescent mental health together in post-divorce counselling.